2014
DOI: 10.1099/mic.0.064675-0
|View full text |Cite
|
Sign up to set email alerts
|

In Bacillus subtilis LutR is part of the global complex regulatory network governing the adaptation to the transition from exponential growth to stationary phase

Abstract: The lutR gene, encoding a product resembling a GntR-family transcriptional regulator, has previously been identified as a gene required for the production of the dipeptide antibiotic bacilysin in Bacillus subtilis. To understand the broader regulatory roles of LutR in B. subtilis, we studied the genome-wide effects of a lutR null mutation by combining transcriptional profiling studies using DNA microarrays, reverse transcription quantitative PCR, lacZ fusion analyses and gel mobility shift assays. We report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 53 publications
0
17
3
Order By: Relevance
“…Upon starvation, SinR-mediated repression of slrR is released, due to which SlrR subsequently stimulates tapA expression. In addition to SlrR, there is another regulator, LutR, that directly regulates tapA expression, while it only indirectly affects eps expression (65). Thus, even though tapA expression and eps expression are in part regulated by the same regulatory proteins, there are many small regulatory differences that could explain our results (see Fig.…”
Section: Figmentioning
confidence: 47%
“…Upon starvation, SinR-mediated repression of slrR is released, due to which SlrR subsequently stimulates tapA expression. In addition to SlrR, there is another regulator, LutR, that directly regulates tapA expression, while it only indirectly affects eps expression (65). Thus, even though tapA expression and eps expression are in part regulated by the same regulatory proteins, there are many small regulatory differences that could explain our results (see Fig.…”
Section: Figmentioning
confidence: 47%
“…BslA is an amphiphilic protein involved in forming a hydrophobic surface layer of biofilms. The expression of bslA is regulated by multiple regulators such as DegU, AbrB and LutR (Verhamme et al, 2009; Ostrowski et al, 2011; Irigul-Sonmez et al, 2014), but it has not been reported which sigma factor controls the transcription of bslA . We also found a SigD-binding motif upstream of the TSS of bslA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such kinds of transcription factors respond to stimuli by acting on distinct regulons [89]. The regulatory roles of LutR, encompassing a broad range of physiological activities in B. subtilis were recently documented [90].…”
Section: Research Papermentioning
confidence: 99%